Program Integrasi Tahfizh Al-Qur’an dalam Kurikulum Madrasah Ibtidaiyah untuk Pembentukan Karakter Siswa - Zulkipli Nasution (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
This study aims to analyze the integration of the Al-Qur'an memorization program in the development of the Madrasah Ibtidaiyah curriculum and its application to the formation of student character. This study uses a qualitative approach with the type of library research, which is sourced from books, scientific journals, and relevant documents related to Islamic education, curriculum, and Al-Qur'an memorization. The data collection technique is carried out through documentation studies, while data analysis uses the content analysis method with the stages of data reduction, data presentation, and conclusions. The results of the study indicate that the integration of the Al-Qur'an memorization program in the Madrasah Ibtidaiyah curriculum can be done through an integrative model, habituation, and a structured special program. This integration plays an important role in shaping student character, such as discipline, patience, responsibility, and religiosity. In addition, the success of implementation is influenced by supporting factors such as teacher competence, institutional commitment, and parental involvement, as well as several obstacles such as time constraints and variations in student abilities. Thus, the integration of Al-Quran memorization in the curriculum is an effective strategy in creating education that not only focuses on cognitive aspects, but also the formation of students' Qur'anic character.